2019
DOI: 10.5005/jp-journals-10024-2536
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Various Tongue Cleaning Aids in the Reduction of Tongue Coating and Bacterial Load: A Comparative Clinical Study

Abstract: Aim: To remove tongue biofilm and improve breath odor, specific instruments (tongue scrapers) or toothbrushes are used. Materials and methods: This study compared the effectiveness of a manual toothbrush that has a tongue scraper on the back of its head and two commercially available tongue scrapers in reducing the tongue coating and aerobic and anaerobic microbiota of the tongue dorsum. A randomized, negative controlled, double-blind, parallel design study for three different treatment interventions was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…64 A recent study showed that plastic or metal tongue scrapers significantly reduced WTCI scores, and anaerobic bacterial count, compared with a manual toothbrush with a tongue scraper. 65 The greatest reduction in bacterial load on the dorsum of the tongue was achieved using plastic tongue scrapers. 65 Another recent study has proposed a specific tongue cleaning technique, the X technique, for reducing the tongue biofilm and organoleptic scores in individuals with intra-oral halitosis, to improve users' perceptions of their breath.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…64 A recent study showed that plastic or metal tongue scrapers significantly reduced WTCI scores, and anaerobic bacterial count, compared with a manual toothbrush with a tongue scraper. 65 The greatest reduction in bacterial load on the dorsum of the tongue was achieved using plastic tongue scrapers. 65 Another recent study has proposed a specific tongue cleaning technique, the X technique, for reducing the tongue biofilm and organoleptic scores in individuals with intra-oral halitosis, to improve users' perceptions of their breath.…”
Section: Treatmentmentioning
confidence: 99%
“…65 The greatest reduction in bacterial load on the dorsum of the tongue was achieved using plastic tongue scrapers. 65 Another recent study has proposed a specific tongue cleaning technique, the X technique, for reducing the tongue biofilm and organoleptic scores in individuals with intra-oral halitosis, to improve users' perceptions of their breath. 66 A Cochrane review reported a small but statistically significant reduction of VSC levels with the use of tongue scrapers or cleaners, rather than toothbrushes, to reduce halitosis in adults.…”
Section: Treatmentmentioning
confidence: 99%
“…The study by Dwivedi showed a significant change in coated tongue assessment with the activity before and after brushing the tongue (P=0.001). [27] This shows that brushing tongue activity has an important role in controlling the growth and the number of bacteria that can affect the growth of coated tongue. Brushing tongue activity can increase the ability of the sense of taste and decrease the potential for bad breath.…”
Section: Resultsmentioning
confidence: 98%
“…Brushing tongue activity can increase the ability of the sense of taste and decrease the potential for bad breath. [27] The number of respondents who have brushing the tongue activity with the coated tongue score of 1 is still low so that the role of medical personnel to improve the quality of life in the age group of over 45 years old is required. The activities carried out are eduction and demonstration on how to maintain oral health.…”
Section: Resultsmentioning
confidence: 99%
“…Lidah, salah satu organ yang berperan penting dalam fungsi pengunyahan, memiliki struktur permukaan yang berbeda dengan enamel gigi sehingga penggunaan pembersih lidah (seperti tongue scraper atau bagian belakang kepala sikat gigi) lebih direkomendasikan daripada menggunakan bulu sikat gigi. 9,10 Hasil dari tindakan menjaga kesehatan gigi dan mulut mahasiswa Undip umumnya berada dalam kategori sedang. Berdasarkan jawaban responden, tindakan berupa kunjungan dan pemeriksaan ke dokter gigi secara teratur serta penggunaan dental floss masih minim dilakukan.…”
Section: Bahasanunclassified